The history of philosophy - Grayling, A. C (Penguin Press, 2019)
"The first authoritative and accessible single-volume history of philosophy to cover both Western and Eastern traditions, from one of the world's most eminent thinkers The story of philosophy is the story of who we are and why. An epic tale, spanning civilizations and continents, it explores some of the most creative minds in history. But not since the long-popular classic Bertrand Russell's A History of Western Philosophy, published in 1945, has there been a comprehensive and entertaining single-volume history of this great, intellectual, world-shaping journey. With characteristic clarity and elegance, A.C. Grayling takes the reader from the worldviews and moralities before the age of the Buddha, Confucius and Socrates through Christianity's capture of the European mind, from the Renaissance and Enlightenment on to Mill, Nietzsche, Sartre and, finally, philosophy today. Bringing together these many threads that all too often run parallel, he surveys in tandem the great philosophical traditions of India, China and the Persian-Arabic world"--